Pengabdian Masyarakat Pada UMKM Toko Baju Tulipfits.Id Dalam Mengimplementasikan Teknologi Platform Shopee - Syallaysyah, Jenny Dwi; Zoniarti, Zoniarti; Rahman, Abdul; Fitriano, Yun; Kurniawan, Kiemas (Jurnal Dehasen Untuk Negeri, 2024)
This socialization aims to describe the community service process carried out at the Tulipfits.id Clothing Shop MSME in implementing Shopee marketplace technology. A qualitative approach is used to explore the challenges and opportunities faced by MSMEs in the adoption of this technology. The development of information technology has changed the scope of marketing. This happens because traditional and conventional marketing methods have been incorporated into the digital world. Marketing that uses advanced digital technology is called digital marketing. Therefore, we conducted community service at one of the MSMEs, Toko Baju Tulip, to help MSMEs introduce their products to the general public using Shopee's digital marketing channel. The purpose of this community service project is to implement online marketing strategies through a web-based digital marketing system. This will also increase the market share of Toko Baju Tulip. The implementation uses focus group discussions (FGDs), observation, interviews, and documentation.